Green Innovation in Young Entrepreneurship: A Global Bibliometric Study - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study presents a global bibliometric analysis of "Green Innovation in Young Entrepreneurship" to explore the intersection of sustainability, entrepreneurship, and youth education. Through keyword co-occurrence, co-authorship, and citation network analyses, the study highlights the increasing academic focus on the role of young entrepreneurs in driving sustainable innovation. The research identifies key themes such as "green entrepreneurship," "sustainable development," and "entrepreneurship education," revealing a growing body of literature that emphasizes the importance of educating young entrepreneurs to address global environmental challenges. Despite significant progress in this research domain, challenges remain, particularly in integrating training and e-learning systems into the entrepreneurial ecosystem. The study underscores the need for a more inclusive and diverse approach to support young entrepreneurs, especially in emerging economies, as they contribute to building a sustainable future.